Preliminary feasibility study of energy and material recovery for Kayu Madang landfill - Tneh, Jia Yung (2015)
Ineffective waste management that involves dumping of waste in landfills may degrade valuable land resources and emit methane gas (CH4), a more potent greenhouse gas than carbon dioxide (C02). However, municipal solid waste (MSW) management in Malaysia is still highly dependent on landfills, as in the case of the MSW management in Kota Kinabalu, Sabah. Because of the concern for greenhouse gases (GHG) emission, scarcity of land and challenges to the development of a green and sustainable future, waste-to-energy (WTE) has become a promising strategy catering to these issues. This is because the utilisation of waste reduces the amount of landfilled waste while increasing renewable energy production. This study aims to evaluate the four selected WTE technologies for MSW management from the aspect of energy, economic and environmental (3E). The material properties of the MSW, its energy conversion potential and subsequent carbon emissions are analysed. An existing landfill, Kayu Madang landfill is selected as the case study for consideration to adopt the advanced WTE technologies. The study presented an interactive comparison of different WTE scenarios and followed by 3E feasibility assessment, with a reference case study in Taman Beringin landfill as the basis calculation for energy potential and net carbon emission. The 3E assessment results indicated incineration as the superior technology choice in terms of energy production; however, MBT is found to be more favourable and sustainable option due to the highest economical benefit with optimal GHG mitigation and energy potential, and in relative to the MSW composition in Kayu Madang.